TALKING TO MACHINES, WRITING THE SELF: A DISCOURSE ANALYSIS OF AI-ENHANCED LITERARY LITERACY AMONG VOCATIONAL STUDENTS - Safii, Muhammad; Hadi, Wisman; Harahap, Muharrina (Journal of Pragmatics and Discourse Research, 2025)
In the age of digital education, artificial intelligence (AI) has emerged as a promising tool to improve literary literacy, particularly among vocational high school students who often perceive literature as abstract or irrelevant. This study investigates the impact of AI-enhanced learning on students’ engagement with literary texts, reframing the research through a discourse analysis lens. We collected data through interviews and classroom observations at SMK Swasta Al Ma'shum Kisaran, using a qualitative phenomenological method. Students interacted with AI platforms to generate, evaluate, and discuss literary content. While results confirm that AI increased student motivation, improved access to information, and provided personalized feedback, this study extends beyond surface-level outcomes by analyzing how discourse practices shifted during learning. Students described AI as an "expert" or “companion,” reflecting new relational discourses between humans and machines. AI feedback embedded implicit discourses of authority, clarity, and guidance, which students often mimicked in their writing. Furthermore, literary production became a space of identity negotiation, with students using metaphor, cultural reference, and narrative framing increasingly sophisticatedly. Immediate feedback from AI not only reinforced language patterns but also shaped students’ self-perceptions as readers and writers. This research contributes to the emerging field of digital discourse studies by illustrating how AI functions not merely as a tool but as a discursive partner in education. Educators must take into account the linguistic and technological aspects of AI integration to foster critical and reflective language use through digital literacy. Future studies should look into how different forms of communication and identity are shaped in learning environments that use AI, across various educational settings.